ANALISIS PERILAKU IMPULSIVE BUYING DALAM PENGGUNAAN E-COMMERCE PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Livianisa, Sheryn; Syamsuri, Syamsuri; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to understand the impulsive buying behavior in the use of e-commerce among students of the Economics Education Program at FKIP Untan and to identify the factors that cause impulsive buying behavior in the use of e-commerce among these students. This research uses a qualitative approach with a case study method. Data collection techniques include interviews, observations, and documentation. The research informants consist of ten students from the Economics Education Program at FKIP Untan. The results show that (1) students of the Economics Education Program at FKIP Untan frequently make impulsive purchases on e-commerce platforms, especially Shopee. (2) These impulsive purchases are generally made without planning, influenced by emotional impulses, attractive promotions, and social influences such as recommendations from friends. Although this behavior provides temporary satisfaction, many students regret their purchasing decisions because the items they buy are often not truly needed. Factors contributing to impulsive buying among these students include mood, social media influences such as TikTok and Instagram, e-commerce promotions such as discounts and free shipping, recommendations from friends, and more stable financial conditions. Impulsive buying occurs more frequently among students with low self-control and when their financial conditions are stable, such as at the beginning of the month